Word Art + Gesture Art = Tone Art: The Relationship Between the Vocal and the Instrumental in Different Arts - Heister, Hanns-Werner; Polk, Hanjo; Rusam, Bernhard (Springer International Publishing, 2023)
This book offers a truly interdisciplinary discussion on the relationship between the vocal and the instrumental in music and other arts and in everyday communication alike. Presenting an in-depth systematical and historical analysis of the evolution of word and gesture art, it gives extensive information on the anthropological, biological, and physiological influences and interactions in music and beyond. The book gives a unique definition of the genuinely vocal and instrumental from their generative deep structure: They derive from and are determined in their production by the duality of voice and hands, and in terms of product as the tone or ‘tonal’ on the one hand, and the percussive, that is noise plus rhythm, on the other. This book succeeds in bringing together perspectives from art, and from natural and social sciences, merging them to offer new explanations about the relationship between the vocal and instrumental, and eventually about the origins of music, arts, and language. It offers new perspectives on the intertwining between the vocal and the instrumental, specifically in the context of the expressions of human languages. At the same time, this book aims at clarifying and explaining the role of words and gestures in different contexts, such as society and communication, education, and arts.